Complete sequence of human mitochondrial DNA obtained by combining multiple displacement amplification and next-generation sequencing on a single oocyte. (4th March 2017) - Ancora, Massimo; Orsini, Massimiliano; Colosimo, Alessia; Marcacci, Maurilia; Russo, Valentina; De Santo, Maria; D'Aurora, Marco; Stuppia, Liborio; Barboni, Barbara; Cammà, Cesare; Gatta, Valentina
Abstract: Mitochondrial DNA (mtDNA) plays a key role in the development of a competent oocyte. In this study, the complete mtDNA sequence obtained for the first time by multiple displacement amplification approach in combination with next-generation sequencing from a single human oocyte is reported (GenBank accession no. KT364276). The analysis of oocyte mitochondrial mutations could provide a better understanding of the genetic variants correlated with the oocyte quality.